TWO DECADES OF KPI RESEARCH: A BIBLIOMETRIC MAPPING AND TREND ANALYSIS - Taib, Nor Asiah; Muhammad, Izlawanie; Hamid, Suhaila Abdul (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
The growing need for transparency, responsibility, and data-driven decision-making has fueled global interest in Key Performance Indicators (KPIs) as key tools for assessing performance across industries. Despite the increasing use of KPIs in business and academia, the extant literature does not provide a thorough overview of their intellectual structure, topic development, or research trends. This study fills the gap by doing a bibliometric analysis of KPIs-related publications over the last two decades, resulting in a systematic map of worldwide scholarly output, collaboration patterns, and conceptual evolution. The dataset was retrieved from the Scopus database and covers the years 2005 to July 2025. A total of 724 documents were detected, cleaned, and standardised using OpenRefine, followed by performance analysis using Scopus Analyser and science mapping with VOSViewer. The analysis looked at publishing trends by year, author, country, and subject area, as well as keyword co-occurrence and international collaboration patterns. The findings show a consistent increase in publication output, with significant contributions from China, the United Kingdom, and the United States. Engineering, computer science, business, and medicine emerged as the most influential disciplines in KPIs research. International collaborative networks were especially prominent in developed economies, demonstrating the global and multidisciplinary importance of KPIs research. This study maps the current state of the KPIs literature and identifies prospects in technology-integrated performance measurement. The findings are an invaluable resource for scholars, practitioners, and policymakers seeking to understand the evolution of KPIs research and propose crucial topics for further exploration.